Selective Separation of L-Aromatic Amino Acid by L-Phenylalanine-Crosslinked Chitosan Resin - Zhang, Jie; Zhou, Xiaohua; Wang, Dan; Wang, Yonghong; Chen, Lin; Tan, Shiyu (Asian Journal of Chemistry, 2013)
Selective separation of L-aromatic amino acid from amino acids mixture solution by L-phenylalanine-crosslinked chitosan resin (PCCR) was investigated in this study. L-Phenylalanine-crosslinked chitosan resin was successfully synthesized via the reaction between glutaraldehyde semi-crosslinked chitosan and L-phenylalanine. L-Phenylalanine-crosslinked chitosan resin could be considered as a macroporous anion exchanger with hydrophobic interaction. The p-p hydrophobic interaction was acted as an auxiliary function to improve the separation process. The optimum operating conditions were studied by batch adsorption and dynamic adsorption of L-phenylalanine on PCCR. The results were as following: the concentration of L-phenylalanine was 3 mg/mL, pH was 6 and flow rate was 3 mL/min. L-Phenylalanine could be eluted effectively using 30 % ethanol with 0.05 mol/L NaOH and flow rate was 0.5 mL/min. The results indicated that L-phenylalanine could be effectively separated from amino acids mixture by PCCR. The recovery rate of pure L-phenylalanine was 78 %. The hydrophobic interaction and electrostatic interaction between the L-phenylalanine and PCCR played an important role in the selective adsorption.